Weak solutions to the 3D steady flow of a compressible reactive mixture. (21st November 2017) - Guo, Boling; Xie, Binqiang; Xi, Xiaoyu
Abstract: The existence of weak solutions to the steady compressible, multicomponent, chemically reacting gas is established without any restriction on the size of the data in the bounded 3D domain with slip boundary conditions. We extend the result in Zatorska (2011 Nonlinearity 24 3267–78) for the adiabatic ratio γ > 7 3 to γ > 2 . Our proof relies upon the weighted estimates of pressure and kinetic energy.